2017
DOI: 10.1007/s11356-017-8800-4
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and desorption characteristics of endosulfan in two typical agricultural soils in Southwest China

Abstract: Endosulfan is an organochlorine pesticide widely used in Southwest China. In this paper, the adsorption and desorption characteristics of endosulfan in two typical agricultural soils (latosol and lateritic red soil) in this area were studied. The results showed that Langmuir isothermal equation could well describe the adsorption thermodynamic characteristics of endosulfan in latosol and lateritic red soil, and the maximum adsorption capacities of α-endosulfan were 0.186 and 0.209 mg/g, while those of β-endosul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The migration ability of pesticides in the soil is associated with their adsorption in the soil 24 and the strength of the adsorption of pesticides mainly depends on the properties of the pesticide and the nature of the soil 25 , 26 . The lower the water solubility of the pesticide, the higher is its adsorption in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…The migration ability of pesticides in the soil is associated with their adsorption in the soil 24 and the strength of the adsorption of pesticides mainly depends on the properties of the pesticide and the nature of the soil 25 , 26 . The lower the water solubility of the pesticide, the higher is its adsorption in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…For example, biodegradation is the main path of niclosamide degradation in natural environments, as aerobatic and anaerobic naturalized microorganisms have a high capability to degrade niclosamide [43]. Factors including oxygen, temperature, soil moisture, soil pH, and soil porous structure influence pesticide microbial degradation [31,42,44,46]. For example, the enantioselective degradation of benalaxyl is mainly influenced by pH, with a greater degradation in soils with higher pH values [47].…”
Section: Pesticide Degradationmentioning
confidence: 99%
“…Some soil factors, including pH, organic matter [42,53,57,58], and soil amendment [59], impact the adsorption of pesticides. Moreover, soils rich in organic matter or clay are much more adsorptive to pesticides than coarse, sandy soils, because clay or organic soils either have a greater particle surface area, or more sites onto which insecticides can be bound [45,55,60,61] For example, the adsorption and desorption abilities of endosulfan may be related to the contents of clay and organic matter in the soil [46,62]. The study shows the sorption/desorption and mobility of strobilurin fungicides in three Chinese soils in the order of Jiangxi red soil > Taihu paddy soil > Northeast China black soil.…”
Section: Pesticide Migration 621 Sorptionmentioning
confidence: 99%
“…Pan et al found that the application of biomass charcoal significantly improved soil fertility and increased the ability of soil to adsorb and fix procymidone [20]. The adsorption and desorption behaviors of procymidone in the soils are consistent with the reported pesticides, including methyl-parathion, endosulfan, atrazine, and carbofuran [21][22][23][24][25]. Bajeer et al reported similar adsorption behaviors of triazophos in different Pakistan soils.…”
Section: Discussionmentioning
confidence: 61%